+0  
 
0
92
1
avatar

g(x)=(3/(x^2)-16)+(2/x+4) ..

 

a.) g^1(x) (g inverse x =..?)

b.) g^1(5)= ?

 

I'm Indonesian BTW :D

Guest Mar 15, 2018
 #1
avatar+87600 
+1

g(x)   = y

 

y  =       3                    2 (x - 4)

        _______    +      _________

        x^2 - 16             (x + 4)(x - 4)

 

y  =    3 + 2x - 8

        __________

          x^2  - 16

 

y  =  2x -  5

       _______

       x^2  - 16

 

y (x^2 - 16)  = 2x - 5

yx^2 - 16y  = 2x - 5

16y  =  yx^2 - 2x + 5

16y  = y (x^2 - (2/y)x + 5/y)

16 =  x^2  - (2/y)x + 5/y      complete the square on x

16  = x^2 - (2/y)x + 5/y + 1/y^2 - 1/y^2 

     

Add  1/y^2  to both sides....subtract 5/y from both sides

 

16 + 1/y^2 -5/y   = x^2 -(2/y)x + 1/y^2      factor the right side

16 + 1/y^2 - 5/y  = (x - 1/y)^2

1/y^2 - 5/y + 16  =  (x - 1/y)^2      get a common denominator on the left

[16y^2 -5y + 1] / y^2  =  (x - 1/y)^2      take both roots

±√[ (16y^2 -5y + 1) / y^2 ]  =  x - 1/y      add 1/y to both sides

1/y ±√  (16y^2 -5y + 1) / y

[ 1 ±√  (16y^2 -5y + 1)  ] / y  = x       "swap" x and y

 

 

[ 1 ±√ [ 16x^2 - 5x + 1) ] / x  =  y  =  g-1(x)

Thus....this is the inverse.....but it is not one-to-one.....we have two values for g-1(5)

g-1 (5)  =   ( 1 + √ [ 16(5)^2 - 5(5) + 1 ] )  / 5   = ( 1 + √ 376 ) /  5  ≈ 4.078

g-1(5) =  ( 1 - √ [ 16(5)^2 - 5(5) + 1 ] )  / 5   = ( 1 - √ 376 ) /  5  ≈ -3.678

 

So   g-1 (5)   =   ≈4.078    and   ≈ -3.678

 

 

 

cool cool cool

CPhill  Mar 15, 2018

10 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.